Development of Textbook “Translation Theory for Beginners” The book helps Students in understanding translation theory - Yunanfathur Rahman; Ari Pujosusanto; Suwarno Imam Samsul (Nusantara Science and Technology Proceedings)
Since 2020 there has been a translation theory course in the curriculum of the German Studies Department at UNESA. This course is the basis for the skills that will be learned by the students in the following semesters. It is necessary to provide good textbooks as study material for this course. A good textbook is very helpful in preparing the learning process through to the implementation of the learning. Textbook is part of the learning resources. Textbooks are books that are put together for the benefit of the learning process. Textbooks can come from research or the results of a thought about something or a study in a particular field, which are then formulated as learning material. The development of the textbook “Translation Theory for Beginners” is intended to make it easier for students to understand, as it is based on mastering the German language in the third semester. The research and development steps carried out consist of three parts, namely preliminary studies, product development and learning about product tests. Preliminary studies have been carried out and information has been produced which will be used as a reference in planning the development of the "Translation Theory for Beginners" textbook.